THE IMPROVEMENT OF PEDAGOGICAL COMPETENCE OF TEACHERS THROUGH COACHING MODEL APPROACH IN SDN GADING VII SURABAYA - Riyo Darminto (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The supervision to be carried out through PTS is a group supervision with collaborative approach. The purpose of this supervision is to improve the competence of lower-grade teachers in making thematic learning plans. Thus, this research is entitled "Coaching Model Program as an Effort to Increase Pedagogical Competence in SDN Gading VII Surabaya”. Based on researcher’s observations as the school principal, facts and observations in the field, teachers seem to understand the performance evaluation and Academic Supervision that will be carried out by their supervisor. However in reality, particularly after evaluations and supervision, there are still several teachers who do not understand the evaluation and supervision conducted towards their work.